Pengaruh Gaya Kepemimpinan, Kecerdasan Spiritual Dan Struktur Organisasi Terhadap Kinerja Karyawan Kantor PT Pojur Madura United Pamekasan - Sri Pratami Imamia; Muhammad Mansur; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis reserach is an explanatory study which aims to examine and analyze the influence of leadership style, spiritual intelligence and organizational structure on the performance of the employees of PT Madura United Pamekasan. The population in the study were employees of PT Madura United Pamekasan and the sample of this study used a saturated sample technique with a total of 40 employees. The data analysis method used in this research is descriptive analysis, instrument test, normality test, multiple linear regression analysis and hypothesis testing. The results of this study found a conclusion, namely that partially leadership style affects employee performance, spiritual intelligence has no positive effect on employee performance, organizational structure has no positive effect on employee performance, while simultaneously leadership style, spiritual intelligence and organizational structure have a positive effect on employee performance. Keywords : Leadership style, spiritual intelligence, organizational structure, employee perfoemance